PENGARUH DANA ALOKASI UMUM, PENDAPATAN ASLI DAERAH, RETRIBUSI DAERAH DAN PAJAK DAERAH TERHADAP PERTUMBUHAN EKONOMI PADA SUMATERA UTARA - Meta Anggurela; Josua Sahala; Rio Fande; Jholant Bringg Luck Amelia Br Sinaga; Muhammad Raja (JURNAL LENTERA BISNIS, 2025)
Economic growth is an important indicator in measuring the level of community welfare and the success of regional development. This study aims to analyze the effect of the General Allocation Fund (DAU), Regional Original Income (PAD), Regional Retributions, and Regional Taxes on economic growth in North Sumatra Province. The background of this study is based on the fluctuation of economic growth in the region in the period 2020–2022, as well as the importance of optimizing regional revenue sources as part of the fiscal decentralization strategy. DAU, PAD, levies, and regional taxes are considered the main instruments in supporting regional government spending to encourage infrastructure development and public services. This research was conducted through a literature approach that examines previous theories and findings related to the contribution of regional income to economic growth. The results of the study show that the four regional income variables are closely related to increasing regional economic activity. The General Allocation Fund functions as a fiscal equalization tool, while PAD, levies, and regional taxes reflect local fiscal capacity in financing development. Thus, increasing regional income is expected to strengthen economic growth in North Sumatra Province in a sustainable manner.